The Rights and Status of Persons with Disabilities in Administrative Proceedings in the Czech Republic - Frumarova, Katerina (PRAWO i WIĘŹ, 2023)
The author deals with the position of persons with disabilities in proceedings before administrative authorities in the Czech Republic. The legislation here is fragmented, and the author examines the basic principles that govern this area. At the same time, attention is focused on the question of the use of public and private institutes to support persons with disabilities in administrative proceedings. Finally, a significant transition trend from the „substitute decision-making system” to the „Supported or Assisted decision-making” concept is analyzed.